BIOSORPSI Cr(III) PADA BIOSORBEN SERAT SABUT KELAPA TERAKTIVASI SODIUM HIDROKSIDA (NaOH) - Sudiarta, I Wayan; Sahara, Emmy (Jurnal Kimia (Journal of Chemistry); Vol. 5, No. 2 Juli 2011)
Studies on biosorption of chromium (III) on NaOH-activated biosorbent of coconut coir fibre have been carried out. These studies included the determination of optimum concentration of NaOH for activating the biosorbent, the determination of biosorbent acidity, the optimum pH, the contact time of biosorption, and the adsorption isotherm type. The result showed that the NaOH optimum concentration for activation of coconut fiber was 1,2 M. The surface acidity of BBN and B00 were of 9,99 ± 0,17 and 3,17 ± 0,21 mmol/g respectively. The surface specific of BBN and B00 were of 20,21 and 19,14 m2/g respectively. The optimum pH of biosorption Cr(III) on BBN and B00 biosorbent was 3 and the contact time were 30, and 120 minutes. The type of isotherm adsorption for the biosorption of Cr(III) on BBN and B00 biosorbent was isotherm S.
Keywords: Biosorption, Chromium(III), NaOH-biosorbent activated